The correlation between parameters indicating obesity and certain environmental factors - Pintér, Zoltán (Acta Biologica Szegediensis, 2009)
The present study deals with the effects of socio-economic and lifestyle factors on the nutritional status of young adults. 627 university students from the University of Szeged, Hungary participated voluntarily in the survey. In order to illustrate their nutritional status, we determined the body mass index (BMI), the waist circumference (WC) and the waist-to-hip ratio (WHR). According to the BMI, 18.4% of the students are somewhat overweight, 64.8% among them show signs of abdominal fat distribution. Based on the aftereffects of the logistic regression, the most important factors influencing the nutritional status include the parents’ level of education, the meals consumed and the frequency of sweets consumption. Among the parameters pointing to obesity, the BMI is the most precise indicator of the external environmental impacts.